Night Market from H. Lefebvre’s Space as Practiced: The Case of Davao City, Philippines - Raymundo Restor Pavo (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2018)
This paper explores the Roxas Night Market in Davao City as practiced space. Guided by Lefebvre’s (1991) notion of space, the night market is a result of actual and evolving activities of vendors as they subsist in the area for their livelihood, interpret and apply the rules set by the Local Government Unit (LGU) of Davao, and manage their spaces as response to emerging experiences such as the three-month rule of the LGU, and bomb blast in 2016. Given that vendors try to maximize their lot and capitalize on their experiences as survivors of bombing incident, they have demonstrated ways of extending their stay in the night market and invoked their new-found identity as symbols of resilience. Such actuations, in turn, reveal the vendors’ creativity and capacity to rise above the rules of the LGU, and the bombing incident. When gleaned from the perspective of Foucault’s power as discipline and transcendence (1977), the way vendors convert the night market into an arena of practice also underscores their agency to conversely discipline the LGU by demanding that the city administration should do its task in securing the area and provide alternative spaces for the increasing number of vendors in the City.